Optimal Defaults in Online Grocery Shopping: A Secondary Analysis to Explore Impacts in Multiresident Households and Families - Ferrante, Mackenzie J.; McGovern, Lily; Epstein, Leonard H.; Hollis-Hansen, Kelseanna; Leone, Lucia A.; Anzman-Frasca, Stephanie (Journal of nutrition education and behavior, 2024)
To examine whether household type (eg, families with children) moderated the effects of an optimal defaults grocery intervention and examine intervention effects on grocery purchases to be consumed by the participant vs others in the household. Participants (n = 65) diagnosed with or at risk for type 2 diabetes were recruited and randomized into an optimal default online grocery intervention or an online or in-person control group. Grocery receipt data were coded into Dietary Approaches to Stop Hypertension nutritional quality scores, and energy, carbohydrate, and sugar content were calculated. Repeated measures analysis of variance examined household types (eg, single vs multi-resident) as moderators of intervention effects. Parallel models explored foods purchased for the participant and foods purchased for other household members separately. Household type was not a significant moderator of intervention effects on nutritional quality or other nutrients of interest (P > 0.10). The default intervention significantly increased the nutritional quality of groceries purchased across household types and for other household members besides the participant (P < 0.05). Optimal defaults may improve grocery purchases across different household types and extend to others in the household, supporting use across household types.